2020
DOI: 10.36253/phyto-11019
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between endophytic Bacillus amyloliquefaciens GGA and arbuscular mycorrhizal fungi induces plant defense responses against white rot of garlic and improves host plant growth

Abstract: White rot, caused by Sclerotium cepivorum, is a serious and economically important disease of garlic, which leads to losses in the garlic production in most of the tropical, subtropical and temperate areas. Biocontrol potential of an endophytic Bacillus amyloliquefaciens GGA and/or arbuscular mycorrhizal fungi (AMF) against this disease was investigated. The B. amyloliquefaciens GGA exhibited antagonistic activity against S. cepivorum in vitro. Scanning electron microscopy revealed alterations in the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
3
23
0
2
Order By: Relevance
“…In addition, triggering plant immunity was also confirmed. Resistance priming in various crops using arbuscular mycorrhizal fungi has also been extensively studied against different pathogenic fungi [ 28 , 29 ]. Numerous plant defense responses have been reported to be triggered due to mycorrhizal colonization, including the lignification (thickening) of cell walls, the production of fungitoxic polyphenolic substances, induction of pathogenesis-related proteins, and overexpression of many defense-related genes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, triggering plant immunity was also confirmed. Resistance priming in various crops using arbuscular mycorrhizal fungi has also been extensively studied against different pathogenic fungi [ 28 , 29 ]. Numerous plant defense responses have been reported to be triggered due to mycorrhizal colonization, including the lignification (thickening) of cell walls, the production of fungitoxic polyphenolic substances, induction of pathogenesis-related proteins, and overexpression of many defense-related genes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this symbiotic relationship, the fungus partner benefits from the carbohydrates formed by the host via photosynthesis. Additionally, the host plant receives multiple benefits from the fungus partner, including the promotion of the plant’s growth [ 25 ], water and nutrient acquisition [ 26 ], the induction of the plant’s resistance against many abiotic stresses, such as salinity and drought [ 27 ], and by triggering plant immunity against various plant diseases [ 28 ]. Rashad et al [ 29 ] reported a significant overexpression in many polyphenol biosynthetic pathway genes in mycorrhizal sunflower plants colonized with Rhizophagus irregularis and infected with Rhizoctonia root rot.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the findings of EL-Sharkawy et al [ 16 ], who found that the colonization of wheat plants with AMF induced the defense responses against stem rust disease. The application of AMF as biocontrol agents against different fungal, bacterial, and viral plant diseases has been extensively studied by many researchers [ 13 , 18 ]. The mycorrhization of the plant root leads to extensive genetic reprogramming in the plant cell, resulting in a set of physiological modulations that regulate the plant responses to different biotic and abiotic stresses [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the hypersensitivity responses such as cytoplasmic granulation and programmed cell death was also reported in mycorrhizal common bean roots infected with R. solani [ 20 ]. The accumulation of the antioxidant enzymes and defense-related proteins represents another defensive mechanism, which has been reported in different plants in response to mycorrhizal colonization [ 13 ]. Increments in the activity of POD and PPO enzymes reported in this study are in accordance with this information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation